2019
DOI: 10.1186/s12974-019-1436-1
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic ceramide as possible indicator of neuroinflammation

Abstract: Background Neurodegenerative diseases such as Alzheimer’s disease (AD), Parkinson’s disease dementia (PDD), and frontotemporal lobar dementia (FTLD) are characterized by progressive neuronal loss but differ in their underlying pathological mechanisms. However, neuroinflammation is commonly observed within these different forms of dementia. Recently, it has been suggested that an altered sphingolipid metabolism may contribute to the pathogenesis of a variety of neurodegenerative conditions. Especia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 56 publications
1
52
0
Order By: Relevance
“…During in ammation astrocytes are enriched in Cer. They seem to produce the pro-apoptotic Cer d18:1/16:0 (85,86). Further, reactive astrocytes release extracellular vesicle enriched in ceramide that carryAβ peptides (86).These speci c extracellular vesiclesisolated from brains of 5xFAD mice showed to be particularly toxic for neurons.…”
Section: Discussionmentioning
confidence: 99%
“…During in ammation astrocytes are enriched in Cer. They seem to produce the pro-apoptotic Cer d18:1/16:0 (85,86). Further, reactive astrocytes release extracellular vesicle enriched in ceramide that carryAβ peptides (86).These speci c extracellular vesiclesisolated from brains of 5xFAD mice showed to be particularly toxic for neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have shown that sphingolipids play a significant role in the pathogenesis of several neuroinflammatory disorders such as Alzheimer's disease and Parkinson's disease (68,69). During early phases of neuroinflammation, astrocytic sphingolipid alterations, which include an increase in ceramide and decrease in SKs that generate S1P were reported (68,70). More information regarding the role of sphingolipids in neuroinflammation were reviewed previously (68,69,71).…”
Section: Brainmentioning
confidence: 99%
“…During in ammation astrocytes are enriched in Cer. They seem to produce the pro-apoptotic Cer d18:1/16:0 (85,86). Further, reactive astrocytes release extracellular vesicle enriched in ceramide that carry Aβ peptides (86).…”
Section: Discussionmentioning
confidence: 99%